NADZÓR PAŃSTWA NAD DZIAŁALNOŚCIĄ UBEZPIECZENIOWĄ W UNII EUROPEJSKIEJ I W POLSCE - Sangowski, Tadeusz (Zeszyty Prawnicze, 2017)
State’s Supervision over the Insurance Activity in Poland and the European Union Summary The paper tries to answer a question on the status of the adaptation process regarding the state’s supervision over the insurance activity in poland in comparison w ith the solutions applied in this respect on the uniform European insurance market. The comparative analysis shows that Polish solutions in principle do not differ from those applied in the European Union. In Poland, the same as in the European Union, a regulation based on a primary rule of a financial supervision as a type of the hitherto material supervision has been chosen. Further, the Polish system of supervision may be characterised by the following: 1. Consolidation o f the management of the insurance supervision system with the supervision over the pensions system, performed by one body - The Com m ittee of the Insurance Supervision and the Occupational Pensions Funds (Komisja Nadzoru Ubezpieczeniowego i Funduszy Emerytalnych); 2. The supervision covers the activity of insurance agencies and the employees’ pensions programmes; 3. In the transition period more severe conditions have been applied with regard to the personal issues, creation o f the insurance products and costs of the insurance protection.